MicroRNA-145 in Barrett's oesophagus: regulating BMP4 signalling via GATA6. Issue 5 (13th April 2012) - van Baal, Jantine W P M; Verbeek, Romy E; Bus, Pauline; Fassan, Matteo; Souza, Rhonda F; Rugge, Massimo; ten Kate, Fiebo J W; Vleggaar, Frank P; Siersema, Peter D
Abstract : Objective: Barrett's oesophagus (BE) is a metaplastic condition of the distal oesophagus which predisposes to oesophageal adenocarcinoma (EAC). It has been suggested that microRNAs (miRNAs) are involved in the process of development of BE and EAC; however, few functional miRNA data are available. The aim of the study was to perform a tissue-specific miRNA profile and, based on this, to examine the function of miRNA-145 in the oesophagus. Design: miRNA expression profiling using microarray analysis in EAC, BE and normal squamous epithelium of the oesophagus (SQ) was performed and validated using real-time PCR in samples from 15 patients and in situ hybridisation in samples from 10 patients. The proliferative effect of miRNA-145 precursor transfection in the SQ (HET-1A) and BE cell line (BAR-T) was measured. Downstream targets of miRNA-145 were determined by analysing mRNA and protein expression from miRNA-145 transfected cells. Results: Three unique miRNA expression profiles were found in tissue from EAC, BE and SQ, which showed that miRNA-145 was upregulated in BE compared with EAC and SQ. Overexpression of miRNA-145 in HET-1A and BAR-T cells reduced cell proliferation and inhibited GATA6, BMP4 and SOX9 mRNA expression. Furthermore, altered BMP4 signalling was observed in vitro on miRNA-145 overexpression. These effects were blocked when cells were co-transfected with a miRNA-145 specific inhibitor. Additionally, BMP4 incubation of HET-1A cells altered miRNA-145 and GATA6 expression over time. Conclusion: These results imply that miRNA-145 indirectly targets BMP4 via GATA6 and is potentially involved in the development of BE.